Development of Young Children’s Time Perception: Effect of Age and Emotional Localization - Qu, Fangbing; Shi, Xiaojia; Zhang, Aozi; Gu, Changwei (Frontiers in Psychology, 2021)
Time perception is a fundamental aspect of young children’s daily lives and is affected by a number of factors. The present study aimed to investigate the precise developmental course of young children’s time perception from 3 to 5 years old and the effects of emotion localization on their time perception ability. A total of 120 children were tested using an adapted time perception task with black squares (Experiment 1) and emotional facial expressions (Experiment 2). Results suggested that children’s time perception was influenced by stimulus duration and improved gradually with increasing age. Both accuracy and reaction time were affected by the presentation sequence of emotional faces, indicating an effect of emotion localization. To summarize, young children’s time perception showed effects of age, stimulus duration and emotion localization.